Implementation of the Pancasila Student Profile Strengthening Project in Natural and Social Science Learning on Climate Change Material in Elementary Schools - Yulita Dwi Lestari (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Climate change education is one of the theme options offered in the Pancasila Student Profile Strengthening Project as part of the implementation of the Merdeka Curriculum at various levels of education in Indonesia. In the Natural and Social Sciences (IPAS) learning for Grade IV Elementary School, there is material on Climate Change and Its Impact. The principles and approaches used in the Merdeka Curriculum for the implementation of climate change education are FRIENDLY. (Relevan, Afektif, Merujuk Pengetahuan, Aksi Nyata, dan Holistik). Then, the purpose of this research is to describe (1) lesson planning, (2) lesson implementation, (3) and evaluation of Natural and Social Sciences learning on the Climate Change theme for 4th grade Elementary School. This research uses a mixed-methods approach with a convergent parallel design. The primary data for this research consists of observations and interviews with teachers and elementary school principals in Lampung Province to obtain perception data related to the implementation of the Merdeka Curriculum. The data analysis technique used is the convergent parallel mixed methods. The researcher collects and analyzes quantitative and qualitative data simultaneously and independently, then combines the quantitative and qualitative analysis results in the final integration of the research. The research results show that: 1) Learning planning uses the available teaching materials. 2) The implementation of learning is in accordance with the prepared teaching module, which includes initial activities, core activities, and final activities. 3) Learning evaluation uses formative assessment, but not all of it has been implemented, namely diagnostic assessment.